2016
DOI: 10.1016/j.jbiomech.2016.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Full-field measurement of micromotion around a cementless femoral stem using micro-CT imaging and radiopaque markers

Abstract: a b s t r a c tA good primary stability of cementless femoral stems is essential for the long-term success of total hip arthroplasty. Experimental measurement of implant micromotion with linear variable differential transformers is commonly used to assess implant primary stability in pre-clinical testing. But these measurements are often limited to a few distinct points at the interface. New techniques based on microcomputed tomography (micro-CT) have recently been introduced, such as Digital Volume Correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In the following, feature tracking (e.g., see Refs. [217,116,216,62,146]) will not be reviewed. The discussion will focus on different variants of DVC in which mechanical information is gradually included.…”
Section: From Local To Integrated Dvcmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, feature tracking (e.g., see Refs. [217,116,216,62,146]) will not be reviewed. The discussion will focus on different variants of DVC in which mechanical information is gradually included.…”
Section: From Local To Integrated Dvcmentioning
confidence: 99%
“…Some attempts were made (e.g., by adding particles [18,77,25,146] or revealing grain boundaries [135] for x-ray µCT) but at the expense of changing the behavior of the investigated material. This is particularly true when studying ductile of brittle fracture [94].…”
Section: Materials Microstructurementioning
confidence: 99%
“…The distinct medial and lateral contact has been previously observed by Gortchacow et al who also found larger gaps on the anterior and posterior sides of straight stems. However, other groups have shown more contact on the anterior than the posterior side, and therefore this variable may be highly dependent on the surgeon's technique, whereas distinct medial and lateral contact is found in all studies.…”
Section: Discussionmentioning
confidence: 61%
“…The choice of local gap size and micromotion levels was made so as to span the variety of results measured experimentally in a previous study (Malfroy Camine et al 2016). …”
Section: Design Of Experiments Approachmentioning
confidence: 99%
“…The initial and boundary conditions were similar, except for the amplitude and direction of micromotion, which were defined according to the interpolation function of 3D bone-implant micromotion around the stem, measured locally using a micro-CT based experimental technique ( Figure S1) (Malfroy Camine et al 2016). …”
Section: Materials Properties Boundary and Initial Conditionsmentioning
confidence: 99%